1979
DOI: 10.1111/j.1365-2265.1979.tb01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolinduced Secretion of Calcitonin in Chronic Renal Disease

Abstract: Whisky (25-50 ml) increased plasma levels of immunoreactive calcitonin (iCT) in seventeen of nineteen patients with chronic renal failure. The effect was greater in patients with high levels of iCT than in those with normal levels. Changes in plasma iCT were not related to changes in calcium, phosphate or immunoreactive gastrin, but were inhibited by the prior administration of propranolol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…In normal subjects, CT is lower in women than in men [27,[32][33][34] and a further decrease is observed in women after menopause [35,36]. In chronic renal failure CT serum levels increase in both sexes [37][38][39] and this is also observed in our series. Even if CT serum levels were about the half in women than in men, they were still a fold elevated over normal range.…”
Section: Discussionsupporting
confidence: 74%
“…In normal subjects, CT is lower in women than in men [27,[32][33][34] and a further decrease is observed in women after menopause [35,36]. In chronic renal failure CT serum levels increase in both sexes [37][38][39] and this is also observed in our series. Even if CT serum levels were about the half in women than in men, they were still a fold elevated over normal range.…”
Section: Discussionsupporting
confidence: 74%
“…These results have been confirmed in humans (healthy, in dialysis, and with MTC) after oral alcohol consumption (25)(26)(27). Therefore we can suppose that, if acute alcohol intake can increase blood CT levels, chronic consumption would a fortiori reinforce this effect, perhaps inducing C-cell hyperplasia.…”
Section: Discussionsupporting
confidence: 61%
“…Indeed increased CT levels have been reported in physiological forms of C-cell hyperplasia more often encountered in male subjects over 50 years old (10,11), in renal insufficiency (12), nonmedullary thyroid tumors and autoimmune thyroiditis (13)(14)(15), sepsis (16), hypergastrinemia (17), hypercalcemia (18), pseudohypoparathyroidism type IA (19), omeprazole treatment (20,21), and measurement artifacts, especially induced by heterophilic antibodies (22,23). Also, alcohol (24)(25)(26)(27) and tobacco (28,29) may increase CT but this assertion is mainly based on the acute affect of the drug in animals and humans. Therefore we assessed basal CT levels in a population of patients with chronic alcoholism before and after weaning, in order to investigate the effect of chronic alcoholic intoxication on plasma CT levels.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast to this, Kanis et al [10] found that on stimulation with oral ethanol, CT increased signifi cantly and increments were related to the level o f the initial value.…”
Section: Introductionmentioning
confidence: 76%
“…It has also been shown that with increasing age de creasing values for ACT have been reported in men and women [10]. Table II demonstrates In an attempt to obtain more insight in CT releasability in uraemic patients, we tested them by administering a low dose of Ca i.v., which in controls virtually did not change CT concentration.…”
Section: Stimulation Testsmentioning
confidence: 99%